A National Survey of Surgical Chairs to Investigate the Role of Diversity, Equity, and Inclusion Vice Chairs in Departments of Surgery - Katya Kaplow, MPH; Grace Keegan, MD; Suhani S. Patel, MPH; Jasmine Akhtar, BS; Karen B. Vanterpool, MPH, PhD; Carolyn Sidoti, BS; Allan B. Massie, PhD; Robert A. Montgomery, MD, PhD; Dorry L. Segev, MD, PhD; Macey L. Levan, JD, PhD; Kathie-Ann Joseph, MD, MPH, FACS (Annals of Surgery Open, 2025)
Objective:. The aim is to identify surgical department chairs’ perspectives on the role of Vice Chairs for Diversity, Equity, and Inclusion (DEI VCs). Background:. The role of DEI VCs has become increasingly common in departments of surgery. However, the role remains ill-defined, and most who hold the position are the first to serve their department in this capacity. Methods:. A 27-item online survey was administered in September 2023 to department chairs across US-based academic general surgery departments who reported having a DEI VC instated in the department. The survey assessed (1) the role, purpose, responsibilities, and value of the DEI VC, (2) resources allotted to DEI VCs, (3) demographic characteristics of both surgical chairs and DEI VCs, and (4) recommendations to increase the impact of the position within the department. Results:. The survey sample consisted of 22 surgical chairs; White (73%) and men (68%). Twenty (91%) agreed that the DEI VC enhances their ability to fulfill their mission to diversity, equity, and inclusion, but only 12 (57%) said that the DEI VC was given an annual budget. Surgical chairs reported that increasing resources, integrating the position across other departments, and defining measures to evaluate success would increase the impact of DEI VCs. Conclusions:. Surgical chairs with a DEI VC find value in the position and provide a range of resources to support the role. These results should be used as evidence for establishing and funding DEI VCs across US-based academic general surgery departments.